Implementation of Life Cycle Costing in Enhancing Value for Money of Projects - Mohd Rahim, Faizul Azli; Muzafar, S.A.; Zakaria, N.; Zainon, N.; Johari, P.A. (International Journal of Property Sciences (E-ISSN: 2229-8568), 2016)
Life Cycle Costing (LCC) is becoming more important since long-term building owners and clients have begun to demand an estimate evidence of what their cost of ownership will accrue to.LCC is a sophisticated approach to estimating the cost incurred in the future and produce comprehensive costing information. Despite growing awareness of LCC practices and concepts among practitioners, actual implementation of this technique is slow to take hold, especially in the Malaysian construction industry. The concept of LCC seems poorly understood; thus, there is a need to overcome this deficiency in order to successfully deliver LCC in the construction industry. This paper aims to study the implementation of LCC, with the main focus on the design stage towards enhancing overall value for money. The relationships between the factors of LCC implementation that can contribute to project‟s value were investigated. The results of this study revealed several critical factors of LCC that should be taken into account to raise awareness and promote LCC implementation at the design stage among the construction practitioners. The challenges to implementation are also discussed in this study.